A new species of the endemic Madagascan scarab beetle genus, Madecorphnus grebennikovi (Coleoptera: Scarabaeidae: Orphninae): morphological description and DNA barcode - Frolov, Andrey V.; Akhmetova, Lilia A.; Vishnevskaya, Maria S. (Zootaxa, 2020)
A new species of the orphnine scarab beetle genus Madecorphnus Paulian, 1992, Madecorphnus grebennikovi Frolov, Akhmetova & Vishnevskaya, new species, is described from the Marojejy National Park, Sava Region, northeastern Madagascar. The new species can be distinguished from the congeners by the parameres narrowly rounded in lateral view and having a small but distinct lateral teeth, and by the endophallic armature consisting of 1) a long straight sclerite with attached to its end a 2/3 shorted, somewhat curved sclerite, 2) separate smaller, elongate sclerite, and 3) a rather large area of microspinules. The 811 bp long fragment of the mitochondrial gene COI (DNA barcode) is provided as a part of the diagnosis of the new species. An updated key to the Madecorphnus species is given.